1998
DOI: 10.1159/000026159
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Toxin Interaction as a Putative Risk Factor for Parkinson’s Disease with Dementia

Abstract: We had previously examined environmental, sociodemographic and clinical variables as predictors for Parkinson’s disease with dementia (PD + D) and found that lower educational attainment, greater motor impairment and advanced age at disease onset were more common in PD + D than in subjects with Parkinson’s disease without dementia (PD – D). We now explore the hypothesis that genetic traits coupled with nongenetic factors may raise the risk of development of PD + D. The study cohort of 43 PD + D and 51 PD – D s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 37 publications
(56 reference statements)
0
14
0
1
Order By: Relevance
“…monamine oxidase and cytochrome P450 CYP2D6 and CYP1A1) have looked exclusively at the genotype-specific risk, with no examination of concomitant environmental risk factors [33-36, 40, 41]. One study of only PD cases showed evidence for an interaction between pesticide exposure and the P450 CYP2D6 gene in risk for dementia [42], but this finding was only applicable to those who already had PD. The inattention to gene-environment interactions in PD may partly be explained by the difficulty of detecting interactions in small samples, but neglecting gene-environment interactions can also hinder the search for etiologic agents [43].…”
Section: Discussionmentioning
confidence: 99%
“…monamine oxidase and cytochrome P450 CYP2D6 and CYP1A1) have looked exclusively at the genotype-specific risk, with no examination of concomitant environmental risk factors [33-36, 40, 41]. One study of only PD cases showed evidence for an interaction between pesticide exposure and the P450 CYP2D6 gene in risk for dementia [42], but this finding was only applicable to those who already had PD. The inattention to gene-environment interactions in PD may partly be explained by the difficulty of detecting interactions in small samples, but neglecting gene-environment interactions can also hinder the search for etiologic agents [43].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to pesticides assessed with a job-exposure matrix was associated with a twofold increase in risk of AD in a cohort of older individuals living in a vineyardgrowing region of France (16). Occupational pesticide exposure was also associated with vascular dementia (180) and with risk of dementia among PD patients (149). Pesticide exposure was associated with mild cognitive dysfunction in a prospective cohort study of cognitive aging (40).…”
Section: Neurologic Diseasementioning
confidence: 99%
“…Although genetic factors play a role in various NDD [Rocchi et al, 2003;Cordato and Chan, 2004] and are a major current focus of research, occupational and environmental factors contribute to NDD [Semchuk et al, 1992;Seidler et al, 1996;Sobel et al, 1996;Strickland et al, 1996;Davanipour et al, 1997;Liou et al, 1997;McGuire et al, 1997;Feychting et al, 1998;Gorell et al, 1998;Hock et al, 1998;Hubble et al, 1998;Johansen and Olsen, 1998;Savitz et al, 1998a;Tsui et al, 1999;Migliore and Coppede, 2002]. Mounting evidence suggests there are multiple, disparate contributing mechanisms such as oxidative damage, aberrant calcium homeostasis, metabolic compromise, amyloid precursor protein mismetabolism, and neuronal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Where heterogeneity exits, the power to detect associations could be reduced. The antioxidant effects of estrogen in women, for example, could mitigate against the effects of oxidative stressors [Behl and Holsboer, 1998], and a genetic polymorphism in metabolism or detoxification of a neurotoxin could have different distributions in white and black workers [Agzndez et al, 1995;Farrer et al, 1997;Hubble et al, 1998;Headrie et al, 2001]. However, a more important source of heterogeneity is probably exposure differences within nominal occupational categories, particularly for generic industrial occupations.…”
mentioning
confidence: 99%